2015
DOI: 10.2174/1574889810666150702124059
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-based strategies for Diagnosis and Therapy

Abstract: Exosomes are small extracellular vesicles (30-120 nm) of endosomal origin, which are gaining the attention of the scientific community. Originally considered only a waste disposal system, they are now emerging as another class of signal mediators. Exosomes are secreted by any cell type and retrieved in every body fluid, such as blood, urine, saliva and amniotic liquid. Remarkably, their biochemical content includes not only lipids and proteins, but also nucleic acids, mainly miRNA and mRNA, with a few reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 0 publications
0
106
0
2
Order By: Relevance
“…In addition, several recent reports point to a nonuniform distribution of these proteins in all EV subpopulations. 12,30 Importantly, EVs also carry membrane receptors on their surface that are characteristic of the cells that they have been generated from. In addition to their surface molecules, EVs also carry important soluble mediators, such as cytokines, growth factors, and transcription factors.…”
Section: Molecular Properties Of Evsmentioning
confidence: 99%
“…In addition, several recent reports point to a nonuniform distribution of these proteins in all EV subpopulations. 12,30 Importantly, EVs also carry membrane receptors on their surface that are characteristic of the cells that they have been generated from. In addition to their surface molecules, EVs also carry important soluble mediators, such as cytokines, growth factors, and transcription factors.…”
Section: Molecular Properties Of Evsmentioning
confidence: 99%
“…Conventional methods of exosome isolation are based on a series of centrifugation steps to exclude cells and cell debris and require more than 10 hours of ultracentrifugation; however, these remain the most economical protocols, especially when large numbers of exosomes are required [55, 56]. Several commercial kits and patented approaches have been developed to improve and simplify the exosome isolation process; Urbanelli et al [57] comprehensively reviewed exosome isolation methods to date. In brief, exosomes can be isolated via ultrafiltration plus size exclusion chromatography, precipitation with polymers and immunoaffinity purification using magnetic beads.…”
Section: Technology For Detecting Ctcs Cfdna and Exosomesmentioning
confidence: 99%
“…In addition, issues related to ectopic tissue formation, infusional toxicity caused by cells lodged in the pulmonary microvasculature, and cellular rejection or unwanted engraftment, have been reported. 4 Studies have shown that MSCs can achieve a therapeutic effect in vivo via paracrine action 5, 6 and direct differentiation. Subsequent studies indicated that MSC-secreted extracellular vesicles (EVs), including microvesicles (MVs; 0.1–1 mm in diameter) and exosomes (40–100 nm in diameter), 7, 8 may contribute to the therapeutic potency of MSCs by mediating cell–cell micro-communication and transporting paracrine factors during angiogenesis, tissue regeneration and immune regulation.…”
Section: Introductionmentioning
confidence: 99%